Large‐scale patterns of biofilm‐dwelling ciliate communities in a river network: Only small effects of stream order. Issue 5 (22nd December 2017) - Ritz, Stephanie; Eßer, Markus; Arndt, Hartmut; Weitere, Markus
Abstract : Although biofilm‐dwelling microfauna (i.e., small metazoans and protzoans) can play an important role in the flux of matter in running waters, their dynamics, and control within stream networks are as yet poorly understood. Here, we analyzed the longitudinal (from first order stream to large river) dynamics of ciliates associated to hard substrate within a river network. Both ciliate abundance and their taxonomical community structure showed no correlations to stream order, although the community structure of the largest river, the Rhine, differed from those of the other rivers. The abundances of biofilm‐dwelling bacteria, algae, rotifers, and nematodes also showed no correlation with stream order. The above results contrast to the abundances of planktonic algae and bacteria that were significantly and positively correlated with the stream order. The results showed that stream size and the corresponding planktonic resource concentration are not reliable parameters in predicting the abundances and community structures of biofilm‐dwelling ciliates. In fact, local parameters seemed to have stronger effects on benthic microfauna communities. Thus, the impact of small‐scale habitat patterns needs further attention in explaining the community structure of biofilm‐dwelling ciliates.